The impact of multiple major shareholders on corporate innovation - Sun, Yi (2022)
With the rapid growth of the world's economy, innovation is the increasingly significant part of economic development. Innovation is an important motivation for sustainable long-term development and corporations and countries attach great importance to the development of technological innovation. The available literature demonstrates that shareholding structure is a key factor in the performance of business innovation. However, many existing research investigate concentrated and decentralised shareholding structures, and the study of shareholding structures with multiple major shareholders is not well researched. In the modern business environment, multiple large shareholders are a common shareholding structure in many businesses. This study is to evaluate the effect of more than one major shareholder on innovation. In addition, the study focuses on the influence of multiple majority shareholders' supervisory capacity and risk-taking on innovation. The study collects data on Chinese A-share quoted companies for the period of 2010 - 2020. The dataset is based on the China Stock Market Accounting Research database and the Chinese Research Data Services database. The findings suggest that multiple major shareholders may result in reduction in the output of innovation and excessive supervision by multiple major shareholders is a significant cause of decline in innovation output. Excessive supervision can lead to reduction in the corporate risk-taking. Therefore, the study recommends that corporations choose the suitable shareholding structure to achieve the goal of enhancing innovation.